Physical activity and body weight of breast cancer survivors – VICAN national survey. (30th September 2020) - Rey, D; Touzani, R; Monet, A; Bendiane, M K; Bouhnik, A D; Mancini, J
Abstract: Background: Cancer recurrence and poor quality of life are major challenges of the growing population of breast cancer (BC) survivors. International guidelines encourage survivors to engage in regular physical activity (PA) and to maintain a healthy body weight (BW), as both have a proven benefit on survival. Our aims were (1) to describe PA and BW 5 years after a BC diagnosis and (2) to define the predictors of long-term engagement in healthy lifestyle, in a representative sample of French survivors. Methods: The French National VICAN surveys were implemented in 2012 and 2015 among cancer survivors. This analysis focused on 723 women with BC, without progression at 5 years, and who participated in both surveys. The questionnaires dealt with several topics including socioeconomic status, treatments and side effects, psychometric scales and lifestyle habits. Results: Five years after diagnosis, 26% of women reported regular PA, 61% occasional PA and 14% no PA. Moreover, 27% reported a weight gain ≥5kg, and 10% a weight loss ≥5kg. Half of the women had decreased or stopped PA since diagnosis. In logistic regression, long-term regular PA was associated with better mental quality of life (aOR=1.04; 1.01-1.07), no depression (aOR=3.42; 1.21-9.65), higher Post Traumatic Growth Inventory score (aOR=1.02; 1.01-1.04), normal arm mobility (aOR=3.7; 1.6-8.4) and healthy and stable BW since diagnosis (aOR=4.47; 1.61-12.37). Weight gain ≥5kg was associated with younger age (aOR=0.96; 0.93-0.99), higher BW at diagnosis (aOR=1.02; 1.01-1.04), and lymphedema 5 years after diagnosis (aOR=1.69; 1.02-2.83). Conclusions: For BC survivors, mental well-being is essential for successful long-term investment in healthy habits. More psychological and dietary support, and a better management of sequelae are needed in this population. Key messages: For breast cancer survivors, mental well-being is essential for successful long-term investment in healthy habits. More psychological and dietary support, and better sequelae management are needed to help breast cancer survivors to persist in healthy lifestyle.